Framing and Visualising Nationhood: Istiqlal Mosque and the Interiority of the Independence Square, Jakarta - Aryanti, Tutin; Achmadi, Amanda (Interiority, 2024)
Studies on interiority have profoundly shifted the perspective of looking at urban space as a socially constructed architectural product. This study examines the meanings invested by Sukarno, the first president of Indonesia and the patron of the mosque, in Istiqlal Mosque (1962) and the Independence Square using the lens of interiority. Rather than looking at the mosque as a single monument, this study considers the mosque and its time and spatial contexts as an architectural unity to make Sukarno's vision of nationhood manifest through the interiority of the Independence Square area in Jakarta, Indonesia's capital city. This study employed an architectural survey and documentation of Istiqlal Mosque and its surrounding built environment and analysed them using Derrida's (1978/1987) centre and margin theory. It is found that the Istiqlal Mosque was designed as part of the frame that reinforces the meaning of the interior of Independence Square, where the National Monument (1964), Sukarno's major monumental project, stands. Istiqlal Mosque was constructed to claim the newly established nation as the world’s most populous Muslim country and to communicate Sukarno’s idea of uniting Indonesia's diverse cultural and religious backgrounds through religious tolerance while declaring his firm standpoint in the 1960s Cold War.